Measuring Tape-Like Sampling Arm and Drill for Sampling Lunar Regolith. (9th May 2013) - Lu, Wei; Ling, Yun; Song, Aiguo; Zeng, Heng; Ding, Weimin; Xu, Baoguo; Gu, Shipeng
Abstract For the task of shallow lunar regolith sampling, we have designed a novel Measuring Tape-like Sampling Arm and Drill (MTS) which is a kind of flexible robot. The advantages of the sampling arm are that it has a small shrink volume, long working distance, light weight, low power consumption and good adaptivity, which is driven by one motor only. Furthermore, it has a large reverse torque with a short force arm, so the pushing force is large enough for the end-effector to penetrate into the lunar regolith. The sampling head which includes two opposite rotating parts has no-reaction screw force. The vibrator located in the sampling head can vibrate at frequencies ranging from 1 to 42Hz and can result in resonance of the sampling head. Therefore, it can improve the efficiency of thrusting, sampling and casting throw. We have carried out theoretical analysis, simulations and experimental studies and it is has been proved that the sampler can sample quantitatively at a of depth of 10 cm in simulated lunar regolith (model CAS-1), cement and sand.